The Mechanism of Dendrobium officinale as a Treatment for Hyperlipidemia Based on Network Pharmacology and Experimental Validation. (13th April 2022) - Li, Lin-Zi; Wang, Hui-Ying; Huang, Jia-Hui; Liu, Kun; Feng, Xiao-Jie; Wang, Xi-Ming; Zhu, Li-Jie; He, Xing-Lishang; Zheng, Xiang; Li, Hai-Long; Dong, Ying-Jie; Li, Bo; et al.
Abstract : Aim and Objective. Hyperlipidemia is a public health matter of global scale, contributing to a wide range of diseases that can result in severe complications and significant annual mortality. Dendrobium officinale (DO) is an edible plant with a long medicinal history in China. Our previous studies revealed that DO may have therapeutic benefits in lipid disorders. However, the mechanism of its active compounds is still unclear. This research aimed at uncovering the hidden anti-hyperlipidemia mechanisms of DO through network pharmacology and experimental validation. Materials and Methods . The active compounds in DO, their targets, and targets associated with hyperlipidemia were screened across various databases, and the hidden targets of DO in treating hyperlipidemia were forecast. The compound-target (C-T), protein-protein interaction (PPI), and compound-target-pathway (C-T-P) networks of DO were set up with Cytoscape software. The hub genes and core clusters of DO predicted to be active against hyperlipidemia were calculated by Cytoscape. The DAVID database was adopted for Gene Ontology (GO) analysis and KEGG pathway enrichment analysis. Next, we used the high-sucrose-fat diet and alcohol (HFDA)-induced hyperlipidemia rats to evaluate the hypolipidemic effect of DO. Results . In this study, we obtained 264 compounds from DO, revealed 11 bioactive compounds, and predicted 89 potential targets of DO. The network analysis uncovered that naringenin, isorhamnetin, and taxifolin might be the compounds in DO that are mainly in charge of its roles in hyperlipidemia and might play a role by modulating the targets (including PPARG, ADIPOQ, AKT1, TNF, and APOB). The pathway analysis showed that DO might affect diverse signaling pathways related to the pathogenesis of hyperlipidemia, including PPAR signaling pathway, insulin resistance, AMPK signaling pathway, and non-alcoholic fatty liver disease simultaneously. Meanwhile, in the HFDA-induced hyperlipidemia rat model, DO could significantly decrease the level of TC, TG, LDL-c, and ALT in serum, and increase HDL-c as well. The liver pathological section indicated that DO could ease liver damage and lipid cumulation. Conclusion . In summary, the biological targets of the main bioactive compounds in DO were found to distribute across multiple metabolic pathways. These findings suggest that a mutual regulatory system consisting of multiple components, targets, and pathways is a likely mechanism through which DO may improve hyperlipidemia. Validation experiments indicated that DO may treat hyperlipidemia by affecting NAFLD-related signaling pathways.